If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 7 + -5x = 0 Reorder the terms: 7 + 3x + -5x = 0 Combine like terms: 3x + -5x = -2x 7 + -2x = 0 Solving 7 + -2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -2x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -2x = 0 + -7 -2x = 0 + -7 Combine like terms: 0 + -7 = -7 -2x = -7 Divide each side by '-2'. x = 3.5 Simplifying x = 3.5
| 4k-14+3/c=21 | | 5h=2 | | 0=2m-18 | | -0.3f+1.3=4.8 | | -18/y+3 | | (x+16)+(x+22)=231 | | y^2-3y/y+3 | | 5(4x)-1/2x=234 | | 9h+4.5-7h+1.75= | | 6x+3x-3= | | 12+7C=103 | | 21-1y=-87+2y | | 6y-5-2y=-31 | | -2/3n-6=18 | | -7+28m=13(2m-3) | | 2v-54=-1v+21 | | 0.5n+0.3n-0.4n= | | 2x=14+2 | | 12-7y=40 | | 12x+y-x+6y= | | 7x-2x+2-x= | | 6n+10=-44 | | 2/3k=4/3 | | 4x^2+176=0 | | 8p-9=49 | | 2x^2+19+24=0 | | 2x/7-2x=x/2+17/2 | | 12/3+4-24/3x8 | | 5+(2-x)/3=7 | | K/4+5=4 | | 4x-9x=45 | | 2.5y-0.25y= |